Interprofessional Team Training Scenario - Hany Atallah; Barbara Kaplan; Douglas Ander; Bethany Robertson (Association of American Medical Colleges, 2009)
Abstract Introduction This scenario was designed to introduce and improve teamwork skills among medical and nursing students. The scenario includes two cases, one team managing the first case; conducting a handoff to the second team who then manages the remainder of the case. The focus of the debriefing is on teamwork skills that were used during the scenarios and areas for improvement. Obtaining X-rays and EKG's should be obtained by the group intending to use the scenario. Methods The TeamSTEPPS (Team Strategies & Tools to Enhance Performance & Patient Safety) evidence-based teamwork program was used in conjunction with this scenario to provide a 4-hour joint training session for third-year medical students and fourth-year nursing students. Components of team training were purposefully incorporated into the scenario. This exercise is best done using medical and nursing students. It can also be used utilizing attendings and residents and registered nurses. The images for the scenarios must be obtained by the group that intends to use the scenario. Results Preliminary data analysis indicates participants had an overwhelmingly positive response to the training overall. Additionally, they indicated that of the four teaching strategies used, the simulation exercise was the most useful. Furthermore, they felt the scenario was believable, enhanced the content learned from reading/lecture, and clarified important issues and concepts. Preliminary data analysis suggests there were improved effects on teamwork knowledge and identification of teamwork skills. Discussion The significance of this work is to encourage teamwork skills and communication to improve patient safety. The team training event was presented at the Second Annual Spring 2008 TeamSTEPPS Consortium Teamwork in Education for the Healthcare Professional Conference at Duke University. As part of a panel, our educational experience was shared with particular emphasis on using TeamSTEPPS as a platform for inter-professional education.